Transcriptional Regulation of Nanog by OCT4 and SOX2 - David J. Rodda; Joon-Lin Chew; Leng-Hiong Lim; Yuin‐Han Loh; Bei Wang; Huck‐Hui Ng; Paul Robson (2005)
Nanog, Sox2, and Oct4 are transcription factors all essential to maintaining the pluripotent embryonic stem cell phenotype. Through a cooperative interaction, Sox2 and Oct4 have previously been described to drive pluripotent-specific expression of a number of genes. We now extend the list of Sox2-Oct4 target genes to include Nanog. Within the Nanog proximal promoter, we identify a composite sox-oct cis-regulatory element essential for Nanog pluripotent transcription. This element is conserved over 250 million years of cumulative evolution within the eutherian mammals. A Nanog proximal promoter-EGFP (enhanced green fluorescent protein) reporter transgene recapitulates endogenous Nanog mRNA expression in embryonic stem cells and their differentiated derivatives. Sox2 and Oct4 interaction with the Nanog promoter was confirmed through mutagenesis and in vitro binding assays. Electrophoretic mobility shift assays indicate that the Sox2-Oct4 heterodimer forms more efficiently on the composite element within Nanog than the similar element within Fgf4. Using chromatin immunoprecipitation, we show that Oct4 and Sox2 bind to the Nanog promoter in living mouse and human embryonic stem cells. Furthermore, by specific knockdown of Oct4 and Sox2 mRNA by RNA interference in embryonic stem cells, we provide genetic evidence for a link between Oct4, Sox2, and the Nanog promoter. These studies extend the understanding of the pluripotent genetic regulatory network within which the Sox2-Oct4 complex are at the top of the regulatory hierarchy.